Routine Pediatric Vaccination in Pakistan During COVID-19: How Can Healthcare Professionals Help? - Khan, Amjad; Bibi, Asima; Sheraz Khan, Khanzada; Raza Butt, Ayesha; Alvi, Hira Amin; Zahra Naqvi, Ada; Mushtaq, Saima; Khan, Yusra Habib; Ahmad, Nafees (Frontiers in Pediatrics, 2020)
Pakistan is still fighting to overcome vaccine-preventable diseases (VPD). The vaccination coverage in rural children remains unsatisfactory amid various barriers including price, hesitancy, and low level of awareness. COVID-19 has decreased the immunization rate in Pakistan due to restricted movements, shortage of vaccines, and low coverage. During the current pandemic, there are high risks that children may get VPD resulting in another infectious disease catastrophe. There is a dire need to put aggressive measures by the government of Pakistan in time to ensure the optimal vaccine coverage. Public education programs for immunization, telehealth services, the involvement of community pharmacies, and the drive-through vaccination system may help to enhance the vaccination rate during the ongoing health crisis.